Regulating the European Sharing Economy: State of Play and Challenges - Malthe Mikkel Munkøe (Intereconomics, 2017)
The past years have seen an extraordinary proliferation of sharing economy platforms, and the largest platforms have fast become global enterprises with market capitalisations that exceed competitors with “traditional” business concepts. These developments call into question a number of regulatory matters and pose new questions for national and European-level regulators.
Keywords: 330